Adenocarcinoma arising from a heterotopic pancreas in the first portion of the duodenum: a case report - Teruya Minami; Takuro Terada; Takeshi Mitsui; Yasuni Nakanuma (Surgical Case Reports)
Abstract Background Heterotopic pancreas (HP) is defined as pancreatic tissue in organs with no anatomical continuity with the orthotopic pancreas. Based on the number of cases reported in the literature between the year 2000 and 2020, HP is rarely found causing malignant transformation of the duodenum. We herein report a case of adenocarcinoma arising from the HP in the first portion of the duodenum. Case presentation A 77-year-old Japanese man presented to our hospital with epigastric pain. Despite having undergone laparoscopic surgery for early sigmoid colon cancer a month earlier, serum levels of tumor-specific antigens, such as CA19-9, were elevated. After undergoing a series of radiologic examinations, the first portion of the duodenum was found thickened. However, a biopsy of the lesion showed no malignancy. Four months later, follow-up computed tomography (CT) scans showed that the lesion was thicker and involved the gastroduodenal artery (GDA), suggesting tumor invasion. A new biopsy did not detect the malignancy. However, serum tumor-specific antigen levels increased, especially duke pancreatic monoclonal antigen type 2 (5287 U/mL), in the absence of tumor in the orthotopic pancreas. The follow-up CT imaging showed a malignant tumor in the first portion of the duodenum. Five months later, we performed a subtotal stomach-preserving pancreaticoduodenectomy (SSPPD) for duodenal or HP cancer in the first portion of the duodenum, finding a lesion from the pyloric bulbs to the first portion of the duodenum, which invaded the adjacent pancreas and GDA. The pathological examination of the specimens revealed adenocarcinoma arising from HP. Nine months after surgery, no recurrence was found by radiologic imaging or tumor-specific antigen laboratory testing. Conclusions HP adenocarcinoma is rare and difficult to diagnose preoperatively due to its submucosal location. Therefore, a careful follow-up with blood testing and radiologic imaging, as well as diagnostic surgery, is recommended.